1992
DOI: 10.1111/j.1365-2249.1992.tb06482.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells clear virus but augment disease in mice infected with respiratory syncytial virus. Comparison with the effects of CD8+ T cells

Abstract: SUMMARYRespiratory syncytial (RS) virus-specific T cell lines were derived from ihe spleens of BALB/c mice primed by intranasal infeclion with RS virus. The lines were expanded by repealed aniigenic stimulation in vitro, and separated into CD4' and CD8 ' T cell-enriched t raciions by immunomagnetie adhesion. The effects of passive Iransfer of these fractions into RS virus infected mice were observed. The most severe immiinopathological changes were seen in mice receiving CD4' cells. Transfer of CD4\ CDS • or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…Previous work by several laboratories has shown that increased eosinophilia in vvG-and FI-RSV-immunized mice often correlates with enhanced systemic disease as measured by weight loss and illness scores (35)(36)(37)(38). Our data indicate that M2-specific CD8 T cells inhibit RSV vaccine-enhanced pulmonary eosinophilia; however it was unknown whether this reduction of pulmonary eosinophilia would correlate with reduced systemic illness.…”
Section: Discussionmentioning
confidence: 42%
“…Previous work by several laboratories has shown that increased eosinophilia in vvG-and FI-RSV-immunized mice often correlates with enhanced systemic disease as measured by weight loss and illness scores (35)(36)(37)(38). Our data indicate that M2-specific CD8 T cells inhibit RSV vaccine-enhanced pulmonary eosinophilia; however it was unknown whether this reduction of pulmonary eosinophilia would correlate with reduced systemic illness.…”
Section: Discussionmentioning
confidence: 42%
“…It may be that other killing mechanisms or cell types are involved (47), for example, Treg cells, which use granzyme B to resolve inflammation after RSV infection (48), or CD8 cells, which have been shown to kill lymphocytic choriomeningitis virus-infected B cells (49). CD8 T cells have been shown to downregulate the Th2 CD4 T-cell response to RSV (50), and transferring RSV-specific CD8 cells into adult mice has an inhibitory effect on antibody responses (51). However, this does not explain why CD4 and CD8 codepletion enhanced antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…7 and our own unpublished observations), and the transfusion of virus-specific T cells into RSV-infected mice aggravates disease (8). Both CD4 ϩ and CD8 ϩ T cells can eliminate virus and cause immunopathology independently (9), but CD8…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 90%